EARLY WARNING SYSTEM BASED ON LOCAL WISDOM IN THE GORONTALO AREA - Misran Rahman; Muhammmad Muhdi Attaufiq (PT. NALURI EDUKASI PRESS, 2025)
The early warning system based on local wisdom in Gorontalo has the potential and integration with modern technology in disaster management and early detection. Gorontalo is an area that is vulnerable to potential disasters such as floods, landslides, and earthquakes. The local potential of the local community has a hereditary culture that functions as an early warning such as animal observation, natural signs to customary-based conservation practices. Based on observations, there are still many hereditary cultures that have not been well documented so that they affect the sustainability of children and grandchildren in the future. Another factor is that there are still many areas that have not been touched by weather sensor technology or early warning systems, so it needs to be encouraged to become education based on local wisdom. With a system based on local wisdom that has become a culture, it is necessary to integrate this culture in a modern way to be inherited to the community legally. This process is then expected to become documentation for the local community legally so that it can be integrated with technology. The research method is carried out with a qualitative-ethnographic approach focused on exploring the practice of local wisdom with a socio-cultural context. The data collection technique was carried out by an interview process with participatory observation to analyze national and local Gorontalo documents. The expected results are in the form of a database and documentation of gorontao local wisdom in early warning which is carried out based on community conditions.